Regular Consumption of Iron Tablets With Anemia in Pregnant Mothers - Ulin Nafiah (International Journal of Health and Medicine, 2024)
Pregnant mothers are one of the groups vulnerable to malnutrition, as there is an increased nutritional need to meet the needs of the mother and the conceived fetus. During pregnancy, the benefits of taking iron tablets or Fe regularly can increase Hb levels so that pregnant mothers do not subsequently have anaemia and can prevent the occurrence of bleeding at the time of delivery, but there are still many pregnant women who are irregular in taking iron pills up to at least 90 tablets. Objective: This study aims to find out the link between regular consumption of iron tablets and the incidence of anaemia in pregnant women in the village of Margorejo. Methods: The type of surveillance used is analytical observational with a Crosectional approach. The population in this study is a pregnant woman of the third trimester in the village of Margorejo. The sample was taken using a saturated sampling method of 30 respondents. The data analysis used is a know-control correlation test. Results: Research results show that the correlation value is 0.541 and the p-value is 0.015 with a significant value of α 0.05. Conclusion: there is a link between regular consumption of iron tablets and anaemia in pregnant mothers